PENGARUH MODEL PEMBELAJARAN EXAMPLES NON EXAMPLES TERHADAP AKTIVITAS DAN PENGUASAAN KONSEP SISWA - Retna Ayu Utari; Pramudiyanti Pramudiyanti; Berti Yolida (Universitas Lampung, 2013)
This research was intended to increase activity and the students’ comprehension. The design of the research was pretest-posttest group design. The sample of this research was the students of VIIA and VIIB class which was chosen by cluster random sampling. The qualitative data was a description of students’ learning activity and questionnaire of students’ response. The quantitative data was gained by the average of result test which was analyzed using T-Test and U-Test. The result showed that there was an increasing of students’ activity with the average percentage of the observed of 85.41%. Students’ comprehension also had an increasing with the average of pretest (47.34); posttest (53.90); and N-gain (12.45). The result of data analysis showed that N-gain of students’ comprehension in every indicator was 22.57 in C1 and 3.65 in C2. Therefore, the use of examples non examples teaching model was increasing of students’ learning activity and students’ comprehension.Penelitian ini bertujuan untuk meningkatkan aktivitas belajar dan penguasaan konsep oleh siswa Desain penelitian ini adalah pretest-posttest group design. Sampel penelitian adalah siswa kelas VIIA dan VIIB yang dipilih dengan menggunakan teknik cluster random sampling. Data kualitatif berupa deskripsi aktivitas belajar dan angket tanggapan siswa. Data kuantitatif diperoleh dari nilai tes yang di analisis menggunakan uji-t dan uji U. Hasil penelitian menunjukkan bahwa adanya peningkatkan aktivitas belajar siswa dengan persentase rata-rata aktivitas yang diamati sebesar 85,41%. Penguasaan konsep juga mengalami peningkatan dengan rata-rata nilai pretes (47,34); postes (53,90); dan N-gain (12,45). Hasil analisis 22,57 untuk C1 dan 3,65 untuk C2. dengan menunjukan bahwa N-gain pada penguasaan konsep siswa. Dengan demikian, pembelajaran menggunakan model pembelajaran examples non examples meningkatkan aktivitas dan penguasaan konsep siswa.Kata kunci: aktivitas belajar, model pembelajaran examples non examples, penguasaan konsep